FREQUENCY OF FIBROID UTERUS IN MULTIPARA WOMEN IN A TERTIARY CARE CENTRE IN RAWALPINDI - Ibrar, Faiza; Riaz, Shazia; Dawood, Nasira S; Jabeen, Alia (Journal of Ayub Medical College Abbottabad, 2010)
Background: At least 20% of all women and 40% of women over the age of 40 years have uterine leiomyomas. They distort the overlying endometrium and can become extruded or pedunculated (fibroid polyp) in the endometrial canal. The diagnosis of myomas is usually based upon the finding of an enlarged, mobile uterus with an irregular contour on bimanual examination or an incidental finding on transabdominal sonography. The objective of this study was to study the frequency of fibroid uterus in multipara women as observed by physical examination and ultrasonography. Methods: During this descriptive study period all the patients reporting Fauji Foundation Hospital with menstrual irregularity partly and fulfilling the inclusion criteria were included. Results: Out of 140 patients with fibroid uterus presenting to gynaecology department 108 (77.14%) were multiparous while 32 (22.86%) were primiparous. The mean parity was 5. The mean maternal age came to be 46 years. Most common presenting complaint of patients with uterine leiomyoma in this study was menstrual irregularity with menorrhagia in 42 (38.9%), metrorrhagia in 28 (25.9%), polymenorrhagia in 8 (7.4%) patients. The other presenting complaint was abdominal mass which was seen in 25 (23.1%). Conclusion: Multiparous patients were found to have fibroids more frequently than nulliparous in their perimenopausal years, which shows their characteristic slow growth rate. The most common manifestation was menorrhagia. Keywords: Multiparity, Frequency, Fibroid